2007
DOI: 10.1111/j.1472-8206.2007.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk for major depression associated with the short allele of the serotonin transporter promoter region (5‐HTTLPR‐S) and the CYP2C9*3 allele

Abstract: In the present study, we aimed to analyze the potential relevance of the polymorphism in the promoter region of the serotonin transporter (SERT or 5-HTT) gene (5-HTTLPR) and the risk of suffering major depression (MDD) in a population of patients previously genotyped for CYP2C9. Seventy white European psychiatric outpatients suffering from MDD and a group of 142 healthy volunteers (HVs) were studied. The frequency of subjects carrying the 5-HTTLPR-S allele was higher (P < 0.05) among MDD than in HV. The odds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 22 publications
0
22
1
Order By: Relevance
“…The s allele of the 5-HTTLPR polymorphism, which affects the promoter of the 5-HTT gene, causes reduced uptake of the neurotransmitter serotonin into the pre-synaptic cells in the brain [3]. Many studies suggest that the s allele of 5-HTTLPR may confer genetic risk for affective disorder [7], such as major depressive disorder [8][10].…”
Section: Introductionmentioning
confidence: 99%
“…The s allele of the 5-HTTLPR polymorphism, which affects the promoter of the 5-HTT gene, causes reduced uptake of the neurotransmitter serotonin into the pre-synaptic cells in the brain [3]. Many studies suggest that the s allele of 5-HTTLPR may confer genetic risk for affective disorder [7], such as major depressive disorder [8][10].…”
Section: Introductionmentioning
confidence: 99%
“…Five studies of whites [143][144][145][146][147] found no substantial relationships between the 5-HTTLPR genotype and major depressive disorder. In contrast, seven Caucasian [148][149][150][151][152][153][154] and one non-Ashkenazi Jewish [144] studies found that the SS genotype was associated with a modest increase in risk of depression. Furthermore, one Polish [155] and one German [156] studies found that the SS genotype was associated with a significant increase in risk of depression.…”
Section: Major Depressive Disorder and 5-httlpr Polymorphismmentioning
confidence: 99%
“…To this end it may be important to take into consideration the reported increased susceptibility for MDD by carriers of CYP2C9*3 and 5-HTTLPR-S [62], the role of CYP2D6 in susceptibility to Parkinson's disease and the effect of cigarette smoking on this risk [63], as well as the fact that CYP enzymes metabolize endogenous neurotransmitters (e.g., CYP2B6 metabolizes testosterone, CYP2E1 contributes to the metabolism of estrogen and CYP2D6 biotransforms tyramine to dopamine and regenerates serotonin), potentially explaining altered neuropsychiatric profiles reported in EM versus PM subjects [64]. These associations, if confirmed and shown to convey large effects, could introduce bias into retrospective or inappropriately designed PGX studies.…”
Section: Discussionmentioning
confidence: 99%